APPLICATION OF MATHEMATICAL MODELING IN PROSTHETICS ON IMPLANTS (World Bulletin of Public Health, 2025)
Orthopedic treatment of patients with dentition defects using mathematical modeling of prosthetic structures on implants. Predicting long-term results of prosthetics. Since in the last decade, computer technology has achieved tremendous development and is actively used in various industries, including medicine, in particular in dentistry to predict the long-term results of prosthetics on dental implants. Thanks to the use of the mathematical modeling method, it has become possible to achieve effective results in the calculation and further construction of complex mathematical models of biological objects.
Keywords: prosthetics; mathematical modeling; computer technology